1989
DOI: 10.1002/mrm.1910090209
|View full text |Cite
|
Sign up to set email alerts
|

Unified multiple‐feature color display for MR images

Abstract: A display method is proposed in which the spin-lattice relaxation time T1, the spin-spin relaxation time T2, and the proton density rho of each pixel in a MR image are simultaneously expressed in color features in a unified way that allows international standardization. MR images were made from a phantom, a healthy volunteer, and patients in such a way that T1 and T2 and proton density images could be derived. T1 and T2 data were compared with accurate relaxation time measurements of the phantom content. Color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The use of an achromatic intensity scale (gray scale) provides only one dimension for the latter purpose (7,8). Fortunately, the use of a chromatic (color) scale could provide three such dimensions, since three parameters are required to characterize a perceived color (8,9). Color scales are commonly used in many types of biomedical imaging and examples are given in Figure 1, where Figure 1a depicts the ''red temperature'' (top) and ''rainbow'' (bottom) scales, two of the approximately 40 provided in the IDL (Interactive Data Language) software package (Re-search Systems, Inc.; Boulder, CO).…”
Section: Color-scale Theory and Real-space Intimate Combinationmentioning
confidence: 99%
“…The use of an achromatic intensity scale (gray scale) provides only one dimension for the latter purpose (7,8). Fortunately, the use of a chromatic (color) scale could provide three such dimensions, since three parameters are required to characterize a perceived color (8,9). Color scales are commonly used in many types of biomedical imaging and examples are given in Figure 1, where Figure 1a depicts the ''red temperature'' (top) and ''rainbow'' (bottom) scales, two of the approximately 40 provided in the IDL (Interactive Data Language) software package (Re-search Systems, Inc.; Boulder, CO).…”
Section: Color-scale Theory and Real-space Intimate Combinationmentioning
confidence: 99%
“…Many studies have demonstrated a variety of methods for producing color MR images [15,16,[21][22][23][24][25][26][27], with evidence to suggest these techniques have advantages for the reporting clinical radiologist over the traditional greyscale images. Over the last two decades image fusion techniques utilising color overlay to display more than one parameter have become commonplace in clinical radiology.…”
Section: Discussionmentioning
confidence: 99%
“…Kamman et al (4) reported an approach with parametric maps for obtaining a diagnostic characterization with colors. However, their chromatic characterization was different, since they used Tl and T2 maps to define the hue and saturation of each pixel.…”
Section: Discussionmentioning
confidence: 99%